2009
DOI: 10.1172/jci37977
|View full text |Cite
|
Sign up to set email alerts
|

A dyad of lymphoblastic lysosomal cysteine proteases degrades the antileukemic drug l-asparaginase

Abstract: l-Asparaginase is a key therapeutic agent for treatment of childhood acute lymphoblastic leukemia (ALL). There is wide individual variation in pharmacokinetics, and little is known about its metabolism. The mechanisms of therapeutic failure with l-asparaginase remain speculative. Here, we now report that 2 lysosomal cysteine proteases present in lymphoblasts are able to degrade l-asparaginase. Cathepsin B (CTSB), which is produced constitutively by normal and leukemic cells, degraded asparaginase produced by E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
128
0
18

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(153 citation statements)
references
References 42 publications
7
128
0
18
Order By: Relevance
“…As a result, the benefits compared with the use of native asparaginase are reduced. Several studies have shown that the structure of asparaginase permits the introduction of modifications without appreciable loss of enzymatic function (7,22,23). The data we present here may provide a rationale for the generation of novel modified versions of asparaginase.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…As a result, the benefits compared with the use of native asparaginase are reduced. Several studies have shown that the structure of asparaginase permits the introduction of modifications without appreciable loss of enzymatic function (7,22,23). The data we present here may provide a rationale for the generation of novel modified versions of asparaginase.…”
Section: Discussionsupporting
confidence: 52%
“…One study showed that the lysosomal cysteine proteases legumain (or asparagine endopeptidase) and cathepsin B efficiently degrade asparaginase in vitro (7). Consistent with these observations, we recently identified a patient carrying a germline mutation in cathepsin B who showed strongly delayed asparaginase degradation (8).…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…This could be an explanation for the observed variability of ASNase trough activity levels in this trial, bearing in mind that no antiASNase antibodies could be detected in any of the patients. 6 The observed ASNase activity serum levels 3 days after ASNase infusion were comparable with those recorded in older children (1 -14 years) with de novo ALL treated with 5 000 U/m² rASNase every third day during induction treatment of de novo ALL. 4 This means that rASNase doses between 5 000 and 10 000 U/m 2 will lead to comparable trough ASNase serum activity levels in children.…”
Section: Discussionsupporting
confidence: 70%